2019
DOI: 10.1182/blood.2019001088
|View full text |Cite
|
Sign up to set email alerts
|

Early progression as a predictor of survival in marginal zone lymphomas: an analysis from the FIL-NF10 study

Abstract: Marginal zone lymphomas (MZLs) are indolent nonfollicular B-cell lymphomas (INFLs) and have heterogeneous clinical behavior. Recently, time to progression of disease at 24 months (POD24) was identified to stratify overall survival (OS) in follicular non-Hodgkin lymphoma and in INFL. Here, we examined the ability of POD24 to predict subsequent OS in a large, international cohort of MZL as part of the NF10 prospective international registry headed by Fondazione Italiana Linfomi (FIL). POD24 was only calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 16 publications
3
58
1
Order By: Relevance
“…Previous studies, mainly using the randomized controlled trial (RCT) or real-world data, have demonstrated that the surrogate endpoints of EFS and PFS are strongly related to OS at both trial- and individual-level in different lymphoma subtypes [ 26 29 , 32 , 39 41 ]. Consistent with the present finding, the subsequent survival of patients with DLBCL or PTCL who achieved EFS24 or PFS24 is almost equal to that of the age-, sex-, and country-matched general population [ 26 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, mainly using the randomized controlled trial (RCT) or real-world data, have demonstrated that the surrogate endpoints of EFS and PFS are strongly related to OS at both trial- and individual-level in different lymphoma subtypes [ 26 29 , 32 , 39 41 ]. Consistent with the present finding, the subsequent survival of patients with DLBCL or PTCL who achieved EFS24 or PFS24 is almost equal to that of the age-, sex-, and country-matched general population [ 26 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have confirmed the association of PFS24 with OS in trial- and treatment arm-level in RCTs on DLBCL patients treated with immunochemotherapy; its association has been externally validated using the literature-based data from high-quality phase II and retrospective studies [ 40 ]. Similarly, in patients with follicular lymphoma and marginal zone lymphomas [ 39 , 41 ], early progression of disease within 24 months after initial treatment stratified subsequent OS and identifies a high-risk population. Consistent with the present study, these findings highlight the important role of PFS or EFS as early efficacy endpoint in designing prospective trials.…”
Section: Discussionmentioning
confidence: 99%
“…POD24 has been identified as a surrogate marker of OS in patients with indolent B-cell lymphoma, including follicular lymphoma and marginal-zone lymphoma, although these studies evaluated all patients from the time of diagnosis and not just relapsed patients. [26][27][28] While we excluded patients with known transformation at first relapse/progression, we cannot exclude that they may have harboured aggressive lymphoma. However, it is important to note that in our study POD24 did not help identifying patients at higher risk of transformation.…”
Section: Discussionmentioning
confidence: 99%
“…MRD detection for those PR patients has a more important value, and we should enhance the follow-up within this special group of patients. Third, as POD24 plays a more important role in predicting adverse prognosis in indolent lymphomas, including marginal zone lymphoma, 10,18,19 how to identify these high-risk patients earlier has become an urgent issue to solve. Our present study demonstrated that MRD positivity after therapy was a powerful indicator, with almost one-third of MRD-positive patients relapsing within 24 months, providing a strong clue for identifying these high-risk POD24 patients.…”
Section: Discussionmentioning
confidence: 99%